The Punitivism against the verticalization of the Penal System and the support in the idea of the enemy (Research, Society and Development, 2019)
The present research aims at analyzing the punitive subjectivity constructed in the historical unfoldings about the penal system and its materialization in a sort of verticalization. Such a system can be classified as: unidirectional; rigid and without panoramic vision and which are economically illustrated in countries with peripheral capitalism. Using the deductive method and the bibliographical research technique, based on the bibliographic studies of Eugenio Zaffaroni on the subject "The criminal issue". In this sense, the research referred to here is of a minimally progressive and humanistic character, that is, the vision of the "other side" of those who are on the margins of a productive system pleaded for competitiveness and indifference. Thus, the "others" who are not in the planning of the ideal that was based on preconceptions. These, in turn, giving continuity to the stigmata that created what Zaffaroni conceptualizes in its work like "face of the enemy" constructed throughout the history. Therefore, the verticalisation of the penal system is what structures the idea of the enemy and sustains the direct relation between crime and punishment, that is, the punishment of punitivism.